OPTIMALISASI MANAJEMEN BANDWIDTH JARINGAN KOMPUTER DENGAN METODE PCQ (PEER CONNECTION QUEUE) MENGGUNAKAN SIMPLE QUEUE - Saepul Anam, Yusup; Nurdiana, Nunu (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2019)
The purpose of this study is to analyze and optimize bandwidth management at SMK 1 Palasah, with the hope that the distribution of bandwidth can be evenly distributed in each room both the teacher's room and student practice room. The research method used includes the method of analysis (a survey of the current system and interviews directly to the user) and optimizing the bandwidth processing method by configuring the proxy using Simple Queue. The results of the study are the optimal management of the available bandwidth so that the distribution of bandwidth can be the same or the same among all users. The conclusion of this study is to do a bandwidth comparison using the PCQ (Peer Connection Queue) method on a simple queue, then the bandwidth distribution for each user can be in accordance with their needs. so access to the internet is not obstructed.